Mitochondrial creatine kinase is critically necessary for normal myocardial high-energy phosphate metabolism. - Spindler, M; Niebler, R; Remkes, H; Horn, M; Lanz, T; Neubauer, S (2002)
The individual functional significance of the various creatine kinase (CK) isoenzymes for myocardial energy homeostasis is poorly understood. Whereas transgenic hearts lacking the M subunit of CK (M-CK) show unaltered cardiac energetics and left ventricular (LV) performance, deletion of M-CK in combination with loss of sarcomeric mitochondrial CK (ScCKmit) leads to significant alterations in myocardial high-energy phosphate metabolites. To address the question as to whether this alteration is due to a decrease in total CK activity below a critical threshold or due to the specific loss of ScCKmit, we studied isolated perfused hearts with selective loss of ScCKmit (ScCKmit(-/-), remaining total CK activity approximately 70%) using (31)P NMR spectroscopy at two different workloads. LV performance in ScCKmit(-/-) hearts (n = 11) was similar compared with wild-type hearts (n = 9). Phosphocreatine/ATP, however, was significantly reduced in ScCKmit(-/-) compared with wild-type hearts (1.02 +/- 0.05 vs. 1.54 +/- 0.07, P < 0.05). In parallel, free [ADP] was higher (144 +/- 11 vs. 67 +/- 7 microM, P < 0.01) and free energy release for ATP hydrolysis (DeltaG(ATP)) was lower (-55.8 +/- 0.5 vs. -58.5 +/- 0.5 kJ/mol, P < 0.01) in ScCKmit(-/-) compared with wild-type hearts. These results demonstrate that M- and B-CK containing isoenzymes are unable to fully substitute for the loss of ScCKmit. We conclude that ScCKmit, in contrast to M-CK, is critically necessary to maintain normal high-energy phosphate metabolite levels in the heart.